10 Sumoylation of essential cardiac signalling proteins: preliminary evidence. (17th November 2015) - Wills, L; Munro, K; Ballantyne, M; Findlay, J; Graham, D; Baillie, GS
Abstract : SUMOylation is a post-translational modification process involving conjugation of the SUMO protein (small ubiquitin-like modifiers) to lysine residues, which can affect protein structure, function and subcellular location. Previous studies by Hajjar et al . 1 have demonstrated SUMOylation of SERCA2a, a calcium transporting ATPase responsible for calcium ion reuptake during cardiac excitation contraction coupling. It has been shown that SUMOylation preserves the ATPase activity and stability of SERCA2a in both mouse and human cells and that levels of SUMO1 and the SUMOylation of SERCA2a itself is greatly reduced in heart failure. Moreover, reconstitution of SUMO1 via adeno-associated-virus-mediated gene delivery has been shown to maintain expression of SERCA2a as well as improving cardiac function in mice with heart failure. Using sequence analysis, we have identified putative SUMOylation sites on other cardiac signalling proteins (beta2 adrenoceptor, ryanodine receptor, cardiac troponin I, and l-type calcium channel) and present preliminary evidence using peptide array that SUMOylation of these sites may occur. As proof of concept we have raised a specific antibody against the SUMOylated form of cTNI and show that this reagent can recognise the SUMOylated form of the protein in cells. We speculate that SUMOylation of cardiac proteins may be utilised as a biomarker of heart disease or provide a platform for the design of novel therapeutic strategies for heart failure. Reference: Kho C, Lee A, Jeong D, Oh JG, Chaanine AH, Kizana E, Park WJ, Hajjar RJ. SERCA2a (sarcoplasmic reticulum Ca2+ ATPase) cTNI (cardiac troponin I). Nature 2011;477:601–605